A gas sensor based on SnS2 / Au schottky junction, a preparation method thereof and application thereof in NO2 detection
A high-quality Schottky contact interface was constructed in a two-dimensional material gas sensor using a transfer contact method, which solved the problem of interface lattice damage during electrode fabrication and enabled highly sensitive detection of NO2 gas at room temperature. The sensor exhibited a significant improvement in sensitivity for NO2 detection and a simple fabrication process.
Patent Information
- Application Number
- CN202611141638.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2046-07-30
AI Technical Summary
Existing gas sensors based on two-dimensional materials suffer from interface lattice damage due to high-energy atomic bombardment during electrode fabrication, which reduces the Schottky contact effect and consequently leads to insufficient sensitivity at room temperature.
The transfer contact method is used to first prepare electrodes and then transfer SnS2 nanosheets to avoid bombardment by high-energy metal atoms and build a high-quality Schottky contact interface. h-BN nanosheets are fixed on SiO2/Si substrate using dry transfer technology, and high-sensitivity detection is achieved by gate voltage modulation.
Highly sensitive detection of NO2 gas was achieved at room temperature, with an almost exponential increase in sensitivity. The sensor achieved a sensitivity of approximately 6000% for 8.4 ppm NO2 and still reached 3600% for 8 ppm NO2. It also exhibited a discernible response at concentrations as low as 5 ppb, and the preparation process was simple.
Smart Images

Figure CN122671497B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor gas sensor technology, specifically relating to a gas sensor based on SnS2 / Au Schottky junction, its preparation method, and its application in NO2 detection. Background Technology
[0002] In existing gas sensing technologies, traditional metal-oxide-semiconductor (MOS) sensors (such as ZnO and SnO2) have long held a dominant position. However, these sensors typically require a high-temperature environment of 200-400°C to activate the surface reaction, which not only leads to high energy consumption and difficulties in circuit integration, but also severely limits their safe application in hazardous environments such as flammable and explosive environments. Therefore, eliminating the dependence on high-temperature operation and developing low-power, high-efficiency gas sensors that operate at room temperature has become a core breakthrough direction in this field.
[0003] In recent years, two-dimensional van der Waals semiconductor materials with atomic-level thickness and high specific surface area (such as tin disulfide SnS2 with suitable band gap and high electron mobility) have shown great potential in the field of room temperature gas sensing. However, existing gas sensors based on two-dimensional materials still face a critical technical bottleneck in their journey towards practical application: physical damage at the electrode contact interface severely limits the sensitivity of the devices.
[0004] In traditional device fabrication processes, two-dimensional materials are typically transferred onto a substrate first, followed by the deposition of metal electrodes (i.e., "evaporation contacts") on the material surface using processes such as electron beam thermal evaporation. During this high-energy evaporation process, high-energy metal atoms directly bombard the two-dimensional semiconductor surface, generating numerous sulfur vacancies and lattice damage. These defects cause the Fermi level to be strongly pinned at the metal / semiconductor interface, disrupting the Schottky barrier between the metal and semiconductor. This degrades the charge transport mechanism at the interface to a conventional ohmic contact dominated by tunneling. Once an ohmic contact is formed, the device's response to gases degenerates into a simple resistance change, losing the amplification effect of Schottky barrier modulation, ultimately leading to a significant decrease in the sensor's sensitivity to gases. Summary of the Invention
[0005] To address the problem of insufficient sensitivity at room temperature in existing two-dimensional material gas sensors due to interface lattice damage and reduced Schottky contact performance caused by high-energy atomic bombardment during electrode fabrication, this invention provides a gas sensor based on a SnS2 / Au Schottky junction, its fabrication method, and its application in NO2 detection. This invention avoids interface damage through transfer contact engineering, achieves sensitive Schottky barrier modulation, and realizes high-sensitivity detection of NO2 gas at room temperature through gate voltage modulation.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A room temperature gas sensor based on Schottky barrier modulation, the structure of which, from bottom to top, includes: a) SiO2 / Si substrate, wherein the Si wafer is the bottom gate electrode; SiO2 is located above the silicon wafer as an insulating layer; b) Source electrode and drain electrode, wherein the source electrode and drain electrode are disposed above SiO2, the source electrode and drain electrode are Au electrodes, and a channel is formed between the source electrode and drain electrode; c) SnS2 nanosheets are stacked on the source and drain electrodes, forming a high-quality Schottky contact interface between the SnS2 nanosheets and the underlying metal electrode, which is not damaged by high-energy metal atoms.
[0007] Furthermore, h-BN nanosheets are further disposed on the SiO2 layer.
[0008] Furthermore, the SnS2 nanosheets have a thickness of 24-26 nm.
[0009] This invention also provides a method for fabricating the aforementioned room temperature gas sensor based on Schottky barrier modulation, employing a "transfer contact method" process, the specific steps of which include: Step 1: Substrate cleaning: Select a silicon wafer with SiO2 on its surface as the substrate, and ultrasonically clean it in acetone, anhydrous ethanol and deionized water for 15 minutes each, then blow it dry for later use. Step 2: On the cleaned SiO2 / Si substrate, spin-coat photoresist, expose and develop it with ultraviolet light to obtain the electrode pattern, then thermally evaporate and deposit the Au layer under high vacuum, remove excess metal by acetone stripping, clean and dry to obtain Au source and drain electrodes with fixed channel spacing. Step 3: Mechanically peel off thin SnS2 fragments from the bulk SnS2 single crystal and transfer them to the PDMS substrate surface for later use via hot pressing. Step 4: The PDMS substrate carrying SnS2 is inverted and fixed on a three-dimensional transfer platform. Under a microscope, the SnS2 nanosheets are precisely aligned and connected across the channel region between the Au source and drain electrodes. After being heated and bonded, the PDMS is slowly separated, and the SnS2 nanosheets are transferred to the target location by utilizing the difference in van der Waals forces.
[0010] Furthermore, step one also includes: dry transfer technology to fix h-BN nanosheets onto a cleaned SiO2 / Si substrate: PDMS carrying h-BN is placed upside down on a three-dimensional transfer platform, suitable h-BN nanosheets are selected and aligned with the SiO2 / Si substrate, heated and bonded, and then the PDMS is slowly separated. h-BN is transferred to the SiO2 surface using van der Waals forces.
[0011] Furthermore, the specific operation of fixing h-BN nanosheets onto a cleaned SiO2 / Si substrate using dry transfer technology is as follows: (1) The PDMS with the h-BN sample is inverted and fixed on the glass slide fixture of the three-dimensional transfer platform, and the pretreated SiO2 / Si substrate is placed flat on the sample stage below. Using a long focal length microscope, h-BN nanosheets of suitable size and thickness are selected, and they are precisely aligned with the center area of the SiO2 surface using a three-dimensional translation stage to reserve operating space for subsequent photolithography and other processes.
[0012] (2) Slowly raise the sample stage to ensure complete contact between the h-BN nanosheets on the PDMS and the SiO2 surface. Then turn on the heating to about 110°C, and adjust the time according to the material properties and the thickness of the PDMS. This step softens the PDMS, removes interfacial bubbles, ensures transfer integrity, and enhances the van der Waals forces between h-BN and SiO2.
[0013] (3) The sample stage is lowered very slowly while the sample is heated to separate the PDMS from the substrate. The reduced adhesion of PDMS at high temperature and the stronger van der Waals interaction between h-BN and SiO2 are used to ensure that the h-BN nanosheets are completely retained on the SiO2 layer.
[0014] Furthermore, the specific operations of the photolithography process in step two are as follows: (1) Spin coating of photoresist: Spin coating of photoresist on the surface of SiO2 / Si substrate that has completed h-BN transfer. To ensure the uniformity of the photoresist film, a spin coater is used for two-stage spin coating: the first stage is low-speed rotation (300 rpm, lasting 10 s), and the second stage is high-speed rotation (4000 rpm, lasting 30 s). (2) Pre-baking: Place the sample on a heating stage and bake at 90°C for 30 seconds. The purpose is to remove residual solvent in the photoresist, enhance the adhesion between the photoresist and the substrate (including the h-BN surface), and allow the photoresist film to solidify and set.
[0015] (3) Using an ultraviolet lithography machine, precisely align the electrode pattern on the photomask with the h-BN nanosheets on the substrate under a microscope, and ensure that the photomask is in close contact with the sample. After confirming that the alignment is correct, turn on the ultraviolet light source for exposure.
[0016] (4) Post-baking: Post-baking is performed immediately after exposure for 30 seconds. Purpose: To promote chemical reactions in the exposed areas (such as cross-linking or decomposition) and improve development contrast.
[0017] (5) Development and fixing: Immerse the sample in the matching developer for about 20 seconds, then transfer it to ultrapure water for rinsing and fixing for about 10 seconds. Finally, gently blow dry the surface moisture of the sample with a clean nitrogen stream to obtain a sample with a specific photoresist pattern.
[0018] Furthermore, the specific operation of the thermal evaporation deposition process in step two is as follows: (1) Fix the photolithographic sample after exposure and development onto the sample stage of the thermal evaporation coating instrument. Start the equipment and evacuate to a high vacuum state to create a clean and low-scattering environment for subsequent evaporation coating.
[0019] (2) Using high-purity Au as the evaporation target, a metal film of the required thickness is uniformly deposited on the surface of the insulating substrate at a constant deposition rate, preferably 20 nm. Purpose: To form a continuous metal layer covering the entire area on the sample surface, including the photoresist opening area (i.e., the electrode pattern area) and the unexposed photoresist area.
[0020] (3) Metal stripping: The coated sample is completely immersed in a glass container containing acetone solution. The acetone dissolves the photoresist in the unexposed areas, causing the excess metal layer attached thereto to fall off; while in the exposed areas (electrode pattern areas), since there is no photoresist to block it, the metal is directly bonded to the substrate and thus retained.
[0021] (4) Cleaning and drying: After the stripping is completed, rinse the residual solvent with ultrapure water in sequence. Finally, blow the sample surface with clean airflow to obtain Au source and drain electrodes with fixed channel spacing.
[0022] Furthermore, the specific steps for step three are as follows: (1) Preparation of PDMS substrate: The curing agent and PDMS (polydimethylsiloxane) solution were mixed at a ratio of 1:10 (mass ratio) and thoroughly stirred using a magnetic stirrer. Then, it was spread evenly in a petri dish and placed in a vacuum environment to remove internal air bubbles. Finally, it was placed on a heating plate and heated at 70°C for 2 hours to allow the colloid to fully cure. It was then cut into cubes of appropriate size for later use.
[0023] (2) Mechanical exfoliation of SnS2 nanosheets: A suitable amount of bulk SnS2 single crystal was placed on a piece of 3M tape, and then another clean piece of 3M tape was used to repeatedly fold, adhere, and tear it. Through multiple cleavages, the material thickness was gradually reduced, and finally, thinner SnS2 fragments were obtained. Subsequently, the tape with SnS2 was smoothly adhered to the prepared PDMS substrate, and the two were placed on a heating stage at 100°C. The PDMS and tape were pressed quickly for 10 seconds, and then the tape was quickly pulled off, leaving SnS2 nanosheets of appropriate size and thickness on the PDMS surface for later use.
[0024] Furthermore, the specific steps for step four are as follows: (1) The PDMS containing the SnS2 sample was inverted and fixed on the glass slide holder of the three-dimensional transfer platform. The composite substrate of the Au source and drain electrodes was placed flat on the sample stage below. Using a long focusing microscope, SnS2 nanosheets of suitable size and thickness were selected; by finely adjusting the three-dimensional translation stage, the SnS2 nanosheets were precisely connected across the two Au source and drain electrodes and completely covered the channel area.
[0025] (2) Slowly raise the sample stage below until the SnS2 nanosheets on the PDMS are completely adhered to the surface of the target electrode. After adhesion, turn on the heating function. Purpose: To eliminate air bubbles introduced during the transfer process, ensure the integrity of the transferred material, and enhance the van der Waals forces between SnS2 and the Au electrode and h-BN.
[0026] (3) While maintaining the heating state, the sample stage is lowered extremely slowly to separate the PDMS substrate from the composite substrate below. Separation principle: The van der Waals force between SnS2 and Au electrode and bottom h-BN is greater than the adhesion force between SnS2 and PDMS, so the SnS2 nanosheets are successfully retained at the target position.
[0027] The dry transfer process effectively avoids the interface defects introduced by high-energy metal atom bombardment in traditional metal evaporation. A high-quality van der Waals Schottky contact interface without lattice damage is constructed between the SnS2 and Au electrodes.
[0028] In traditional vapor deposition methods, high-energy Au atoms bombard the SnS2 surface, causing lattice damage. Dry transfer, on the other hand, involves no high-energy particles, preserving the intrinsic electronic structure and interface characteristics of SnS2, which is beneficial for forming high-quality Schottky contacts.
[0029] The present invention also provides the application of the room temperature gas sensor based on Schottky barrier modulation in NO2 detection.
[0030] Furthermore, the sensor achieves reversible detection of NO2 under 470nm illumination with an intensity of 0.4mW / cm². 2 .
[0031] Furthermore, the sensor has a NO2 detection concentration range of 5 ppb-10 ppm.
[0032] Furthermore, the sensor exhibits a linear relationship between sensitivity and NO2 concentration in the range of 0.5-8 ppm.
[0033] Furthermore, the source-drain voltage V of the sensor DS =1V, gate voltage V G =0V.
[0034] The beneficial technical effects of this invention are as follows: This invention reduces physical damage to the SnS2 crystal and interface, which is beneficial for forming high-quality Schottky contacts. This invention abandons the traditional process of evaporating electrodes onto the material surface, and instead uses a transfer contact method of "preparing the electrode first, then transferring the material." This process is relatively mild and can, to a certain extent, avoid lattice impact and damage to the SnS2 surface by high-energy metal atoms, suppressing Fermi level pinning. This helps to construct a high-quality metal / semiconductor Schottky contact interface, providing a favorable physical basis for subsequent high-sensitivity detection.
[0035] A near-exponential increase in sensitivity was achieved using barrier modulation. Thanks to a relatively intact Schottky barrier, the interfacial barrier height changes significantly when gas adsorption alters the semiconductor surface potential, thus amplifying the response to trace gas molecules. Experiments show that under room temperature and dark conditions, the sensor achieves a sensitivity of approximately 6000% for 8.4 ppm NO2; under 470 nm illumination, the sensitivity for 8 ppm NO2 remains at 3600%, and it still exhibits a discernible response of approximately 15% at concentrations as low as 5 ppb. This device is simple to fabricate and its performance far surpasses that of gas sensors using SnS2 as the single adsorbent material.
[0036] This invention proposes a detection process that first compares the response / recovery characteristics under dark conditions and 470nm illumination, and then applies gate voltage modulation after selecting the illumination conditions. Sensitivity is high in the dark but recovery is relatively poor; under 470nm illumination, although sensitivity decreases somewhat, it remains at an acceptable level, while recovery is significantly improved. Furthermore, by adjusting the gate voltage to near 0V under 470nm illumination, faster recovery can be achieved while maintaining high sensitivity.
[0037] This invention preliminarily elucidates the mechanism by which gate voltage regulates channel carrier concentration and the Schottky barrier. Results show that when a 0V gate voltage is applied, the two can reach a relatively balanced state. At this point, the device is more sensitive to changes in the Schottky barrier height (relatively high sensitivity), and the recovery time is also shorter (approximately 70 seconds), which helps to achieve rapid and continuous gas monitoring. Attached Figure Description
[0038] Figure 1 This is a schematic diagram of the device in Example 1.
[0039] Figure 2 This is a schematic diagram of the device in Example 2.
[0040] Figure 3 This is a schematic diagram of the device in Comparative Example 1.
[0041] Figure 4 This is an optical microscope photograph of the device in Example 1.
[0042] Figure 5 This is an optical microscope photograph of the device in Example 2.
[0043] Figure 6 This is an optical microscope photograph of the device in Comparative Example 1.
[0044] Figure 7 The physical Raman spectroscopic characterization of the device in Comparative Example 1 is shown.
[0045] Figure 8 The physical Raman spectral characterization of the device in Example 1 is shown.
[0046] Figure 9 The physical atomic force microscope characterization of the device in Comparative Example 1 is shown.
[0047] Figure 10 The physical atomic force microscope characterization of the device in Example 1 is shown.
[0048] Figure 11 The images are high-resolution transmission electron microscopy (TEM) images and their corresponding selected area electron diffraction (SAED) patterns.
[0049] Figure 12 This is a transmission electron microscope image of the cross-section of the device at the gold electrode interface in Example 1.
[0050] Figure 13 This is a cross-sectional transmission electron microscope image of the device in Example 1 at the interface of the SiO2 substrate.
[0051] Figure 14 The measurements of the device in Comparative Example 1 were taken in a dark environment. I DS - V DS curve.
[0052] Figure 15 The measurements were taken by the device in Example 1 in a dark environment. I DS - V DS curve.
[0053] Figure 16 The device in Example 1 under different NO2 concentrations I DS - V DS curve.
[0054] Figure 17 Comparative Example 1 device under different NO2 concentrations I DS - V DS curve.
[0055] Figure 18 The Schottky barrier height of the two devices varies with NO2 concentration.
[0056] Figure 19 The device in Example 1 is based on Figure 16 The curve showing the change in sensitivity of the extracted material with NO2 concentration.
[0057] Figure 20 For Comparative Example 1 device according to Figure 17 The curve showing the change in sensitivity of the extracted material with NO2 concentration.
[0058] Figure 21 The image shows the dynamic response curve of the device in Example 1 to 1ppm NO2 in a dark environment and under 470nm laser irradiation.
[0059] Figure 22 The results measured by the device in Example 1 at different NO2 concentrations I DS - V G Transfer characteristic curve.
[0060] Figure 23 The image shows the dynamic response curve of the device in Example 1 under 470nm illumination with NO2 concentrations ranging from 5ppb to 8ppm.
[0061] Figure 24 The image shows the dynamic response curves of the device in Example 1 to 8ppm NO2 under 470nm illumination and different gate voltages.
[0062] Figure 25 For the device in Example 1 Figure 24 The response / recovery time of the device extracted from the sample to 8ppm NO2.
[0063] Figure 26 This is to demonstrate the long-term stability of the NO2 response signal of the device in Example 1 over a 15-day period.
[0064] Figure 27 This is a selective test of the device in Example 1 for interfering gases.
[0065] Figure 28 The physical atomic force microscopy characterization of the device in Example 2 is shown.
[0066] Figure 29 The physical Raman spectral characterization of the device in Example 2 is shown.
[0067] Figure 30 For Example 2, the device was used in a dark environment. V DS =1V I DS- V G Transfer characteristics.
[0068] Figure 31 The device in Example 2 was tested in a dark environment and under light intensity of 0.4 mW / cm². 2 Measured under 470nm illumination I DS - V DS curve.
[0069] Figure 32 Example 2 device under 0ppm and 1.4ppm NO2 environments, and after 20 min of desorption. I DS - V DS curve.
[0070] Figure 33 The device in Example 2 was tested at different NO2 concentrations from 0 to 8 ppm. I DS - V DS The curve, and the 470nm illumination (0.4mWcm) 2 The corresponding sensitivity extracted from the data.
[0071] Figure 34 The devices of Examples 1 and 2 were tested at a light intensity of 0.4 mW / cm². 2 Comparison of dynamic sensing behavior under 470nm illumination.
[0072] Figure 35 This document summarizes the sensitivity of the devices from Examples 1 and 2 on different substrates.
[0073] Figure 36 For the device in Example 2, the gate voltage V G Sensitivity from -30V to 20V, with a light intensity of 0.4mW / cm² 2 Measured under 470nm illumination I DS - V DS The curve was extracted.
[0074] Figure 37 For the device in Example 2 V G The relationship between sensitivity and NO2 concentration at -30V, 0V and 20V.
[0075] Figure 38 The device in Example 2 operates at a light intensity of 0.4 mW / cm². 2The responses to 2.5 ppm and 9 ppm NO2 were measured under 470 nm illumination in N2 and air environments.
[0076] Figure 39 The device in Example 2 operates at a light intensity of 0.4 mW / cm². 2 NO2 sensing behavior with a wide dynamic range from 50ppb to 9ppm under 470nm illumination.
[0077] Figure 40 The device in Example 2 is based on Figure 39 The relationship between extraction sensitivity and NO2 concentration.
[0078] Figure 41 The cyclic response of the device in Example 2 to 0.5 ppm and 2.5 ppm NO2 for three consecutive cycles is shown.
[0079] Figure 42 This is a comparison of the device's response to NO2 and its responses to H2S, NH3, and CO2 in Example 2.
[0080] Figure 43 This is an optical microscope photograph of the SnS2 / Au device in Example 3.
[0081] Figure 44 Physical atomic force microscopy characterization of the SnS2 / Au device in Example 3.
[0082] Figure 45 For along Figure 44 The height profile curve of the device is obtained at the location shown.
[0083] Figure 46 The image shows the dynamic response curves of the SnS2 / Au device in Example 3 under different NO2 concentrations. Detailed Implementation
[0084] Example 1: T-SnS2 / Au Sensor The sensor, from bottom to top, comprises: a silicon substrate; a SiO2 layer on the silicon substrate, serving as physical support and the bottom gate; a 300nm SiO2 / Si substrate formed by the silicon substrate and the SiO2 layer; a source electrode and a drain electrode located on the surface of the SiO2 / Si substrate; gold electrodes for both the source and drain electrodes; a 20μm wide channel between the source and drain electrodes; and tin disulfide (SnS2) nanosheets that are integrally connected above the source and drain electrodes. The SnS2 nanosheets are 26nm thick, and a physically damage-free Schottky contact is formed between the SnS2 nanosheets and the source and drain electrodes.
[0085] Example 2: T-SnS2 / Au / h-BN Sensor The difference between this sensor and the sensor in Example 1 is that the SiO2 layer has h-BN nanosheets, but the rest of the structure is exactly the same.
[0086] Example 3
[0087] The difference between this sensor and the sensor in Example 1 is that the thickness of the SnS2 nanosheet is approximately 86 nm, while the rest of the structure is exactly the same.
[0088] Comparative Example 1: E-SnS2 / Au Sensor The sensor, from bottom to top, includes: A silicon substrate with a SiO2 layer on it forms a 300nm SiO2 / Si substrate. SnS2 nanosheets: 30 nm thick, located on the surface of a SiO2 / Si substrate. Source and drain electrodes were formed by direct deposition on the surface of SnS2 nanosheets via thermal evaporation, with an electrode thickness of 20 nm. The source and drain electrodes form a channel with a width of 20 μm.
[0089] Example 4: Method for fabricating the sensor of Example 1 Step 1: Substrate cleaning: Select a silicon wafer with SiO2 on its surface as the substrate, and ultrasonically clean it in acetone, anhydrous ethanol and deionized water for 15 minutes each, then blow it dry for later use. Step 2: On the cleaned SiO2 / Si substrate, metal source and drain electrodes are fabricated using photolithography and thermal evaporation deposition processes, and a channel region is left between the two electrodes. Step 3: Prepare SnS2 nanosheets using mechanical exfoliation; Step 4: Precisely align the stripped SnS2 nanosheets and imprint them onto the pre-prepared source and drain electrodes using dry transfer technology to form a room temperature gas sensor.
[0090] The specific operations of the photolithography process in step two are as follows: (1) Spin coating of photoresist: Photoresist is spin coated on the surface of SiO2 / Si substrate. To ensure the uniformity of the photoresist film, a spin coater is used for two-stage spin coating: the first stage is low-speed rotation (300 rpm, lasting 10 s), and the second stage is high-speed rotation (4000 rpm, lasting 30 s). (2) Pre-baking: Place the sample on a heating stage and bake at 90°C for 30 seconds. The purpose is to remove residual solvent in the photoresist, enhance the adhesion between the photoresist and the substrate, and solidify and shape the photoresist film.
[0091] (3) Using an ultraviolet lithography machine, precisely align the electrode pattern on the photomask with the h-BN nanosheets on the substrate under a microscope, and ensure that the photomask is in close contact with the sample. After confirming that the alignment is correct, turn on the ultraviolet light source for exposure.
[0092] (4) Post-baking: Post-baking is performed immediately after exposure for 30 seconds. Purpose: To promote chemical reactions in the exposed areas (such as cross-linking or decomposition) and improve development contrast.
[0093] (5) Development and fixing: Immerse the sample in the matching developer for about 20 seconds, then transfer it to ultrapure water for rinsing and fixing for about 10 seconds. Finally, gently blow dry the surface moisture of the sample with a clean nitrogen stream to obtain a sample with a specific photoresist pattern.
[0094] The specific operation of the thermal evaporation deposition process in step two is as follows: (1) Fix the photolithographic sample after exposure and development onto the sample stage of the thermal evaporation coating instrument. Start the equipment and evacuate to a high vacuum state to create a clean and low-scattering environment for subsequent evaporation coating.
[0095] (2) Using high-purity Au as the evaporation target, a metal film of the required thickness is uniformly deposited on the surface of the insulating substrate at a constant deposition rate, preferably 20 nm. Purpose: To form a continuous metal layer covering the entire area on the sample surface, including the photoresist opening area (i.e., the electrode pattern area) and the unexposed photoresist area.
[0096] (3) Metal stripping: The coated sample is completely immersed in a glass container containing acetone solution. The acetone dissolves the photoresist in the unexposed areas, causing the excess metal layer attached thereto to fall off; while in the exposed areas (electrode pattern areas), since there is no photoresist to block it, the metal is directly bonded to the substrate and thus retained.
[0097] (4) Cleaning and drying: After the stripping is completed, rinse the residual solvent with ultrapure water in sequence. Finally, blow the sample surface with clean airflow to obtain Au source and drain electrodes with fixed channel spacing.
[0098] The specific steps for step three are as follows: (1) Preparation of PDMS substrate: The curing agent (Silgard 184 type silicone elastomer curing agent) and polydimethylsiloxane (PDMS) solution were mixed at a ratio of 1:10 (mass ratio) and thoroughly stirred using a magnetic stirrer. Then, it was spread evenly in a petri dish and placed in a vacuum environment to remove internal air bubbles. Finally, it was placed on a heating plate and heated at 70°C for 2 hours to allow the colloid to fully cure. It was then cut into cubes of appropriate size for later use.
[0099] (2) Mechanical exfoliation of SnS2 nanosheets: A suitable amount of bulk SnS2 single crystal was placed on a piece of 3M tape, and then another clean piece of 3M tape was used to repeatedly fold, adhere, and tear it. Through multiple cleavages, the material thickness was gradually reduced, and finally, thinner SnS2 fragments were obtained. Subsequently, the tape with SnS2 was smoothly adhered to the prepared PDMS substrate, and the two were placed on a heating stage at 100°C. The PDMS and tape were pressed quickly for 10 seconds, and then the tape was quickly pulled off, leaving SnS2 nanosheets of appropriate size and thickness on the PDMS surface for later use.
[0100] The specific steps for step four are as follows: (1) The PDMS containing the SnS2 sample was inverted and fixed on the glass slide holder of the three-dimensional transfer platform. The composite substrate of the Au source and drain electrodes was placed flat on the sample stage below. Using a long focusing microscope, SnS2 nanosheets of suitable size and thickness were selected; by finely adjusting the three-dimensional translation stage, the SnS2 nanosheets were precisely connected across the two Au source and drain electrodes and completely covered the channel area.
[0101] (2) Slowly raise the sample stage below until the SnS2 nanosheets on the PDMS are completely attached to the surface of the target electrode. After attachment, turn on the heating function.
[0102] (3) While maintaining the heating state, the sample stage is lowered very slowly to separate the PDMS substrate from the composite substrate below.
[0103] Example 5: Method for fabricating the sensor of Example 2 Step 1: Substrate cleaning: Select a silicon wafer with SiO2 on its surface as the substrate, and clean it by ultrasonic cleaning in acetone, anhydrous ethanol and deionized water for 15 minutes each. Dry it and set it aside. Use dry transfer technology to fix h-BN nanosheets on the cleaned SiO2 / Si substrate. Step 2: On the surface of the SnS2 / Au / h-BN substrate, metal source and drain electrodes are fabricated using photolithography and thermal evaporation deposition processes, and a channel region is left between the two electrodes. Step 3: Prepare SnS2 nanosheets using mechanical exfoliation; Step 4: Precisely align the stripped SnS2 nanosheets and imprint them onto the pre-prepared source and drain electrodes using dry transfer technology to form a room temperature gas sensor.
[0104] In step one, the specific operation of fixing h-BN nanosheets onto the cleaned SiO2 / Si substrate using dry transfer technology is as follows: (1) The PDMS with h-BN sample is inverted and fixed on the glass slide fixture of the three-dimensional transfer platform, and the pretreated SiO2 / Si substrate is placed flat on the sample stage below. Using a long focal length microscope, h-BN nanosheets of suitable size and thickness are selected, and they are precisely aligned with the central area of the SiO2 surface by a three-dimensional translation stage to reserve operating space for subsequent photolithography and other processes.
[0105] (2) Slowly raise the sample stage to ensure complete contact between the h-BN nanosheets on the PDMS and the SiO2 surface. Then turn on the heating to about 110°C, and adjust the time according to the material properties and the thickness of the PDMS. This step softens the PDMS, removes interfacial bubbles, ensures transfer integrity, and enhances the van der Waals forces between h-BN and SiO2.
[0106] (3) The sample stage is lowered very slowly while the sample is heated to separate the PDMS from the substrate. The reduced adhesion of PDMS at high temperature and the stronger van der Waals interaction between h-BN and SiO2 are used to ensure that the h-BN nanosheets are completely retained on the SiO2 layer.
[0107] The specific operations of the photolithography process in step two are as follows: (1) Spin coating of photoresist: Spin coating of photoresist on the surface of SiO2 / Si substrate that has completed h-BN transfer. To ensure the uniformity of the photoresist film, a spin coater is used for two-stage spin coating: the first stage is low-speed rotation (300 rpm, lasting 10 s), and the second stage is high-speed rotation (4000 rpm, lasting 30 s). (2) Pre-baking: Place the sample on a heating stage and bake at 90°C for 30 seconds. The purpose is to remove residual solvent in the photoresist, enhance the adhesion between the photoresist and the substrate (including the h-BN surface), and allow the photoresist film to solidify and set.
[0108] (3) Using an ultraviolet lithography machine, precisely align the electrode pattern on the photomask with the h-BN nanosheets on the substrate under a microscope, and ensure that the photomask is in close contact with the sample. After confirming that the alignment is correct, turn on the ultraviolet light source for exposure.
[0109] (4) Post-baking: Post-baking is performed immediately after exposure for 30 seconds. Purpose: To promote chemical reactions in the exposed areas (such as cross-linking or decomposition) and improve development contrast.
[0110] (5) Development and fixing: Immerse the sample in the matching developer for about 20 seconds, then transfer it to ultrapure water for rinsing and fixing for about 10 seconds. Finally, gently blow dry the surface moisture of the sample with a clean nitrogen stream to obtain a sample with a specific photoresist pattern.
[0111] The specific operation of the thermal evaporation deposition process in step two is as follows: (1) Fix the photolithographic sample after exposure and development onto the sample stage of the thermal evaporation coating instrument. Start the equipment and evacuate to a high vacuum state to create a clean and low-scattering environment for subsequent evaporation coating.
[0112] (2) Using high-purity Au as the evaporation target, a metal film of the required thickness is uniformly deposited on the surface of the insulating layer substrate at a constant deposition rate, preferably with a thickness of 20 nm.
[0113] (3) Metal stripping: The coated sample is completely immersed in a glass container containing acetone solution. The acetone dissolves the photoresist in the unexposed areas, causing the excess metal layer attached thereto to fall off; while in the exposed areas (electrode pattern areas), since there is no photoresist to block it, the metal is directly bonded to the substrate and thus retained.
[0114] (4) Cleaning and drying: After the stripping is completed, rinse the residual solvent with ultrapure water in sequence. Finally, blow the sample surface with clean airflow to obtain Au source and drain electrodes with fixed channel spacing.
[0115] The specific steps for step three are as follows: (1) Preparation of PDMS substrate: The curing agent (Silgard 184 type silicone elastomer curing agent) and polydimethylsiloxane (PDMS) solution were mixed at a ratio of 1:10 (mass ratio) and thoroughly stirred using a magnetic stirrer. Then, it was spread evenly in a petri dish and placed in a vacuum environment to remove internal air bubbles. Finally, it was placed on a heating plate and heated at 70°C for 2 hours to allow the colloid to fully cure. It was then cut into cubes of appropriate size for later use.
[0116] (2) Mechanical exfoliation of SnS2 nanosheets: A suitable amount of bulk SnS2 single crystal was placed on a piece of 3M tape, and then another clean piece of 3M tape was used to repeatedly fold, adhere, and tear it. Through multiple cleavages, the material thickness was gradually reduced, and finally, thinner SnS2 fragments were obtained. Subsequently, the tape with SnS2 was smoothly adhered to the prepared PDMS substrate, and the two were placed on a heating stage at 100°C. The PDMS and tape were pressed quickly for 10 seconds, and then the tape was quickly pulled off, leaving SnS2 nanosheets of appropriate size and thickness on the PDMS surface for later use.
[0117] The specific steps for step four are as follows: (1) The PDMS containing the SnS2 sample was inverted and fixed on the glass slide holder of the three-dimensional transfer platform. The composite substrate of the Au source and drain electrodes was placed flat on the sample stage below. Using a long focusing microscope, SnS2 nanosheets of suitable size and thickness were selected; by finely adjusting the three-dimensional translation stage, the SnS2 nanosheets were precisely connected across the two Au source and drain electrodes and completely covered the channel area.
[0118] (2) Slowly raise the sample stage below until the SnS2 nanosheets on the PDMS are completely attached to the surface of the target electrode. After attachment, turn on the heating function.
[0119] (3) While maintaining the heating state, the sample stage is lowered very slowly to separate the PDMS substrate from the composite substrate below.
[0120] Comparative Example 2: Method for fabricating the sensor used in Comparative Example 1 This comparative example demonstrates the fabrication of a conventional vapor-deposited device. The specific steps are as follows: SnS2 nanosheets are first transferred onto a SiO2 substrate, and then Au metal atoms are directly deposited on the surface of the SnS2 nanosheets to form electrodes using photolithography and thermal evaporation techniques.
[0121] The device schematic diagrams for Embodiments 1 and 2 are as follows: Figure 1-2 As shown, the schematic diagram of the device in Comparative Example 1 is as follows. Figure 3 As shown. Physical diagrams of the devices in Examples 1 and 2 are shown below. Figure 4-5 As shown, the physical diagram of the device in Comparative Example 1 is as follows. Figure 6 As shown.
[0122] I. Characterization of the device in Example 1 and Comparative Example 1 1. Characterization of interface quality: To compare the interface quality between SnS2 nanosheets and Au electrodes, Figure 4 and 6 Raman spectra were collected at position AD in the image. Figure 4 and Figure 6 Positions A and C in the diagram correspond to the original SnS2, while positions B and D represent SnS2 located above or below the Au electrode. In the vapor-deposited E-Au / SnS2 device, position A at the SnS2 / Au interface (position B) represents the SnS2. 1g The full width of the half-peak is 8.03cm. -1 The full width at half maximum (FWHM) of the transferred T-SnS2 / Au device at the corresponding interface (location D) is significantly narrower, at 7.30 cm⁻¹. -1 This indicates that the damage-free dry transfer method significantly reduces the interface defect density introduced by high-energy Au atom bombardment during metal evaporation. In the E-Au / SnS2 device, the A of the original SnS2 (position A) 1g The peak intensity is only slightly lower than the intensity measured below the vapor-deposited Au electrode (position B), and the intensity is higher than I. B / I A 1.6 ( Figure 7 In stark contrast, for T-SnS2 / Au devices, the original SnS2 (position C) has an A 1g The intensity is much weaker than the intensity on the Au electrode (at position D), with a ratio I. D / IC Reached 4.14 ( Figure 8 The significant enhancement of Raman intensity in T-SnS2 / Au devices stems from the suppression of interface defects at the metal-semiconductor interface, which optimizes optical coupling and maximizes constructive interference.
[0123] Figure 9 and 10 Atomic force microscopy images of T-SnS2 / Au and E-SnS2 / Au are shown, revealing that the SnS2 nanosheet thicknesses of the E-Au / SnS2 and T-SnS2 / Au devices are approximately 26 nm and 30 nm, respectively.
[0124] Figure 11 Selected area electron diffraction (SAED) patterns and high-resolution TEM images of SnS2 nanosheets are presented. The SAED pattern exhibits a six-fold symmetric diffraction arrangement, confirming a hexagonal lattice structure, while the HRTEM images resolve to clear lattice fringes with a spacing of 0.32 nm. Figure 12 and Figure 13 As shown, the cross-sectional TEM image of the T-SnS2 / Au device at the interface between the Au electrode and the SiO2 substrate confirms that the dry transfer method did not introduce any structural defects into the SnS2 material.
[0125] 2. Influence of preparation process on interfacial contact properties E-SnS2 / Au I DS - V DS The curve exhibits a clear linear characteristic. Figure 14 This indicates the formation of a typical ohmic contact. The reason is that during the evaporation process, high-energy metal atoms bombard the SnS2 surface, generating a large number of sulfur vacancies or lattice damage, resulting in strong pinning of the Fermi level and insignificant barrier modulation.
[0126] T-SnS2 / Au I DS - V DS The curve exhibits obvious nonlinear rectification characteristics. Figure 15 This demonstrates that the gentle transfer operation avoids physical damage, preserves the original semiconductor properties, and forms a high-quality Schottky contact at the Au / SnS2 interface.
[0127] 3. The enhancing effect of Schottky barrier modulation on sensitivity Tests revealed that as the NO2 concentration increased from 0 ppm to 8.4 ppm, the T-SnS2 / Au device ( Figure 16 ) and E-SnS2 / Au devices ( Figure 17The channel currents of both types of SnS2 and NO2 showed a significant decreasing trend. Because NO2 is a strong oxidizing gas, when it adsorbs on the n-type SnS2 surface, it steals electrons. After the electrons are removed, the semiconductor depletion layer widens, which not only increases the semiconductor's own resistance but, more importantly, alters the interfacial potential distribution, significantly increasing the height of the Schottky barrier.
[0128] Based on the Shockley diode equation for the adsorption of NO2 I DS - V DS Curve fitting ( Figure 18 At 0 ppm, the barrier height is approximately 0.6 eV, and when 8.4 ppm NO2 is introduced, the barrier height increases to 0.71 eV. The Shockley diode equation is as follows:
[0129]
[0130] in, I RS It is the reverse saturation current. V DS The voltage applied across the junction, q For elementary charge, R S For series resistance, η As an ideal factor, k B Where is Boltzmann's constant, and T is the absolute temperature. A For the area of the Schottky junction, A * Effective Richardson constant, Φ B For the effective Schottky barrier height.
[0131] The relationship between current and barrier height is exponential; a 0.11 eV increase in barrier height results in a significant drop in current. Test results are as follows... Figures 19-20 As shown, the T-SnS2 / Au device achieved a sensitivity of 6000% when 8.4ppm NO2 was introduced, and exhibited a good linear effect, which was much higher than that of the E-SnS2 / Au device.
[0132] 4. The effect of illumination on sensitivity and restorability and its synergistic modulation with gate voltage To investigate the effect of illumination conditions on sensor performance, the response and recovery curves of T-SnS2 / Au to the target NO2 concentration were first tested under a fixed gate voltage in both dark conditions and under 470nm wavelength illumination with different powers. Figure 21The results showed that in the dark, the device exhibited extremely high sensitivity to NO2 (e.g., approximately 769% sensitivity to 1 ppm NO2), but the recovery after gas removal was extremely slow, with recovery times reaching hundreds of seconds, making it difficult to meet the requirements for continuous monitoring. At 0.4 mW / cm 2 Under 470nm illumination, although the sensitivity decreased somewhat (e.g., to approximately 289% for 1 ppm), it remained significantly higher than that of traditional ohmic contact devices, and the recovery time was significantly shortened to the 70s level, resulting in a substantial improvement in recoverability. Experiments show that the photogenerated non-equilibrium carriers introduced by 470nm illumination help accelerate the desorption process of NO2 molecules, thereby improving recovery characteristics, while the sensitivity loss remains within an acceptable range. Based on the above comparisons, 0.4mW / cm² was determined... 2 The preferred working illumination environment is 470nm light, in order to obtain excellent recovery performance with acceptable sensitivity.
[0133] 5. Gate voltage regulation and determination of the optimal operating point (under 470nm illumination conditions) After selecting 470nm illumination conditions, different bottom-layer gate voltages ranging from -40V to 40V were applied to T-SnS2 / Au. V G ), to test its electrical transfer characteristics and dynamic response ( Figure 22 Through photoelectric synergy, the device exhibits an extremely wide concentration detection range (5 ppb to 8 ppm). Figure 23 The extremely low detection line of 5 ppb NO2 showed a clear sensitivity of 15%, while the response to 8 ppm NO2 reached 3600%. Further analysis revealed dynamic response waveforms for 8 ppm NO2 at different gate voltages (e.g.,...). Figure 24 (as shown) and response / recovery time statistics ( Figure 25 This demonstrates that the sensitivity decreases with increasing gate voltage, and in V G The sensitivity remains high at 0V. This indicates that the channel carrier concentration and Schottky barrier modulation efficiency are optimally balanced at 0V gate voltage, making it most sensitive to barrier changes. Simultaneously, the synergistic effect of 0V gate voltage and 470nm illumination ensures both high sensitivity and the fastest recovery time (97s). Therefore, V G =0V and 470nm illumination were determined to be the optimal test conditions for this invention, achieving the best balance between sensitivity and recoverability.
[0134] 6. Long-term stability and gas selectivity of the device In practical applications, the lifespan and anti-interference capability of sensors are crucial. For example... Figure 26As shown, after 15 days of storage, T-SnS2 / Au underwent dynamic testing again, and the linear fitting curve of sensitivity versus concentration was extracted. The results show that the fitting curve after 15 days highly coincides with the initial preparation state, and no significant performance degradation was observed, demonstrating that the device has extremely excellent long-term stability.
[0135] In addition, selective testing was conducted by introducing interfering gases under the same test conditions. Figure 27 The device exhibits a sensitivity of up to 3700% to 9 ppm NO2, while the response signals to the same concentrations of H2S and NH3 remain negligible even after amplification by 10 times. This demonstrates that the Schottky barrier modulation mechanism of this invention possesses extremely strong selectivity for NO2.
[0136] II. Characterization of the device in Example 2 AFM images of T-SnS2 / Au / h-BN devices are as follows: Figure 28 As shown, the SnS2 nanosheet has a thickness of 24 nm. At position A (the SnS2 at the top of the Au electrode on the h-BN), the full width at half maximum (FWHM) of the Raman A1g peak is 7.32 cm⁻¹. - ¹( Figure 29 ), and 7.2 cm on SiO2 - ¹Comparable. This indicates that the intrinsic quality of the crystals on the two substrates is similar. The Raman intensity at position A on h-BN is nine times that at position B (at the original SnS2 on h-BN). This significant enhancement may be attributed to the reduced interfacial charge scattering on the dangling-bond-free surface of h-BN. The field-effect mobility of the T-SnS2 / Au / h-BN device was extracted from the transfer characteristic curves (see...). Figure 30 The calculated mobility was 8.0 cm. 2 / (V·s), which is much higher than the 0.69 cm⁻¹ of T-SnS₂ / Au devices on SiO₂. 2 / (V·s). These results collectively demonstrate that h-BN provides a superior interface as a substrate.
[0137] Figure 31 Demonstrated performance in both dark and 470nm illumination (0.4mW cm⁻¹) conditions. -2 The IDS-VDS output curve was measured under illumination. Fitting the dark-state IDS-VDS curve using the Shockley diode equation yielded a Schottky barrier height of approximately 0.57 eV and an ideality factor of 2.2. Under illumination, the curve exhibits quasi-ohmic behavior, attributed to photo-induced Schottky barrier suppression. This photo-induced quasi-ohmic contact in the T-SnS2 / Au / h-BN device is fundamentally different from the quasi-ohmic behavior of vapor-deposited E-Au / SnS2 devices, which originates from Fermi level pinning due to interface defects. Figure 32The output curves are shown before and after 10 minutes of exposure to 1.4 ppm NO2. The sensitivity reaches approximately 8500%, highlighting the ultra-high response achieved by the high-quality SnS2 / Au interface. This sensitivity is approximately 9.6 times that of T-SnS2 / Au / SiO2 devices (~880%). However, even after 20 minutes of desorption in the dark, the sensitivity remains as high as 1150%, indicating incomplete recovery due to the strong retention of adsorbed NO2 molecules. Therefore, illumination is required to promote molecule desorption and improve recovery efficiency. Figure 33 To be illuminated at 470nm (0.4mW cm⁻¹) -2 The following series of IDS-VDS curves for NO2 concentrations were obtained, and the sensitivity was extracted from them. Maximum sensitivity reached 10000% at 8 ppm. Dynamic response from 0.5 ppm to 9 ppm was also analyzed. Figure 34 It exhibits extremely high sensitivity under illumination compared to T-SnS2 / Au / SiO2 devices, and the recovery time is less than 100 seconds. Figure 35 The linear response behavior of the T-SnS2 / Au / h-BN sensor was demonstrated. At the same NO2 concentration, the T-SnS2 / Au sensor using h-BN as the substrate showed approximately 2-3 times higher sensitivity than the sensor using only the SiO2 substrate, and both exhibited good concentration linear response characteristics. Among them, the h-BN system showed superior gas sensing performance.
[0138] Figure 36 Under 470nm illumination (0.4mW / cm²) 2 Under these conditions, the sensitivity of the gate voltage extracted from the IDS-VDS curve ranges from -30V to 20V. It can be seen that the gate voltage corresponding to the maximum sensitivity shifts in a more positive direction with increasing NO2 concentration, moving from -10V at 2.1ppm to 0V at 4.2ppm. This trend indicates that at higher NO2 concentrations, a larger gate-sensing electron concentration is required to maintain efficient charge transfer to the adsorbed molecules, thereby achieving maximum sensitivity.
[0139] Figure 37 The linear sensitivity-concentration relationship of the T-SnS2 / Au / h-BN device at different gate voltages is shown, contrasting with the Langmuir-type saturation observed on SiO2. This linear behavior stems from the atomically flat h-BN surface, which provides a high density of uniform adsorption sites.
[0140] To assess whether ambient oxygen interferes with the NO2 response, the sensing performance under 470 nm illumination was compared in pure N2 and ambient air. Figure 38 As shown, under 470nm illumination (10mW cm⁻¹) -2The responses to 2.5 ppm and 9 ppm NO2 in pure N2 and ambient air were compared. In air, the sensitivities were 864% and 2500%, respectively, while in N2 they were 900% and 2500%, respectively. Nearly identical response amplitudes and recovery curves confirmed that ambient oxygen did not cause any perceptible reduction in NO2 sensitivity. Therefore, dynamic response curves were further measured from 50 ppb to 9 ppm. Figure 39 ), and extracted concentration-related sensitivity ( Figure 40 Similar to the T-SnS2 / Au device on SiO2, the T-SnS2 / Au / h-BN device exhibits a Langmuir-to-linear transition, but the transition point shifts from 0.2 ppm on SiO2 to 0.5 ppm on h-BN. The wider Langmuir region on h-BN indicates that the inert h-BN surface suppresses high-affinity defect sites that lead to early saturation on SiO2, allowing Langmuir adsorption on uniform SnS2 surface sites to persist to higher concentrations. To verify long-term stability, measurements were repeated after 10 days. The behavior was completely consistent, with only a slight decrease in sensitivity. Repeatability was further evaluated by performing multiple response-recovery cycles at 0.5 ppm, 2.5 ppm, and 9 ppm NO2. In three consecutive cycles, the device demonstrated excellent cycling stability with average sensitivities of 440%, 2400%, and 9520% at each concentration. Figure 41 Subsequently, the selectivity of the T-SnS2 / h-BN / Au device for 9ppm NO2, 9ppm H2S, 9ppm NH3 and 1000ppm CO2 was evaluated. Figure 42 The sensor exhibits an ultra-high sensitivity of 95.90% for the target gas NO2, while its responses to H2S, NH3, and CO2 are only -13%, -7%, and -32%, respectively (see inset). The corresponding selectivity ratios are approximately 737, 1370, and 300, highlighting the device's excellent specific recognition capability.
[0141] III. Characterization of Example 3 Optical microscope images of the device in Example 3 show that SnS2 nanosheets cover the space between the Au source and drain electrodes, and the device structure is intact. Figure 44 The atomic force microscope image of the device shows that the surface of the SnS2 nanosheet is relatively smooth, and no obvious large-area wrinkles, cracks or serious damage were observed, indicating that the fabricated device has good surface morphology quality. Figure 45 For along Figure 44 The height profile curve obtained at the location shown shows that the thickness of the SnS2 nanosheet is approximately 86 nm.
[0142] Subsequently, the NO2 dynamic gas-sensitive response of the above-mentioned device was tested. For example... Figure 46As shown, the devices exhibited significant dynamic responses within the NO2 concentration range of 0.25–9 ppm, and the device response gradually increased with increasing NO2 concentration.
[0143] Comparison with the device in Example 1 revealed that the sensor's sensitivity significantly decreased as the thickness increased from 26 nm to 86 nm. The thinner sensing layer provided an extremely high response amplitude, attributed to a shorter diffusion path and higher charge transfer efficiency; while the thicker sensing layer resulted in a substantial decrease in sensitivity due to restricted gas diffusion and weakened signal response. This indicates that the thickness of the SnS2 nanosheets can significantly modulate the gas-sensing performance of the device and can serve as an important structural parameter for adjusting device sensitivity.
[0144] In summary, this invention systematically compares two methods: direct evaporation of the Au electrode onto SnS2 (E-Au / SnS2) and dry transfer of SnS2 onto the Au electrode (T-SnS2 / Au). The T-SnS2 / Au device achieves a detection limit of 5 ppb, with a sensitivity of 3600% for 8 ppm NO2 under 470 nm illumination and a dark-state sensitivity of 6000%, which is 100 times that of the evaporation-deposited device. Replacing the SiO2 substrate with h-BN further improves performance: the T-SnS2 / Au / h-BN device exhibits a sensitivity of 8500% for 1.4 ppm NO2 in the dark and a sensitivity close to 10000% for 8 ppm NO2 under illumination. Furthermore, the h-BN device demonstrates excellent long-term stability, with negligible performance degradation after 10 days, and consistent response in both N2 and air. This superior performance stems from the low-defect SnS2 nanosheets, the high-quality metal-semiconductor interface, and the atomically flat h-BN substrate. These three elements work together to suppress Fermi level pinning, enabling effective modulation of the Schottky barrier during NO2 adsorption. These results pave a practical path for high-performance SnS2-based gas sensors for real-world NO2 detection.
Claims
1. A room temperature gas sensor based on Schottky barrier modulation, characterized in that: The structure, from bottom to top, includes: a) SiO2 / Si substrate, wherein the Si wafer is the bottom gate electrode; SiO2 is located above the silicon wafer as an insulating layer; b) Source electrode and drain electrode, wherein the source electrode and drain electrode are disposed above SiO2, the source electrode and drain electrode are Au electrodes, and a channel is formed between the source electrode and drain electrode; c) SnS2 nanosheets are stacked on the source and drain electrodes, forming a high-quality Schottky contact interface between the SnS2 nanosheets and the underlying metal electrode that is not damaged by high-energy metal atoms. The fabrication method of the room temperature gas sensor based on Schottky barrier modulation includes the following specific steps: Step 1: Substrate cleaning: Select a silicon wafer with SiO2 on its surface as the substrate, and ultrasonically clean it in acetone, anhydrous ethanol and deionized water for 15 minutes each, then blow it dry for later use. Step 2: On the cleaned SiO2 / Si substrate, spin-coat photoresist, expose and develop it with ultraviolet light to obtain the electrode pattern, then thermally evaporate and deposit the Au layer under high vacuum, remove excess metal by acetone stripping, clean and dry to obtain Au source and drain electrodes with fixed channel spacing. Step 3: Mechanically peel off thin SnS2 fragments from the bulk SnS2 single crystal and transfer them to the PDMS substrate surface for later use via hot pressing. Step 4: The PDMS substrate carrying SnS2 is inverted and fixed on a three-dimensional transfer platform. Under a microscope, the SnS2 nanosheets are precisely aligned and connected across the channel region between the Au source and drain electrodes. After being heated and bonded, the PDMS is slowly separated, and the SnS2 nanosheets are transferred to the target location by utilizing the difference in van der Waals forces.
2. The room temperature gas sensor based on Schottky barrier modulation according to claim 1, characterized in that: h-BN nanosheets are further deposited on the SiO2 layer.
3. The room temperature gas sensor based on Schottky barrier modulation according to claim 1, characterized in that: The SnS2 nanosheets have a thickness of 24-26 nm.
4. The room temperature gas sensor based on Schottky barrier modulation according to claim 1, characterized in that: Step one of the method also includes fixing h-BN nanosheets onto a cleaned SiO2 / Si substrate using a dry transfer method, and then fabricating source and drain electrodes on the h-BN nanosheets. Specifically, PDMS carrying h-BN is placed upside down on a three-dimensional transfer platform, the h-BN nanosheets are aligned with the SiO2 / Si substrate, and after heating and bonding, the PDMS is slowly separated to transfer h-BN to the SiO2 surface.
5. The room temperature gas sensor based on Schottky barrier modulation according to claim 4, characterized in that: The specific operation of step four is as follows: the PDMS substrate carrying SnS2 nanosheets is inverted and fixed above the three-dimensional transfer platform, and the Au source-drain electrode composite substrate is placed below it; the three-dimensional displacement stage is used to precisely align it and connect it across the channel region between the Au source-drain electrodes; the sample stage is raised to make SnS2 adhere to the electrode, and heating is used to eliminate bubbles and enhance van der Waals forces; the PDMS and the substrate are slowly separated under heating conditions.
6. An application of a room temperature gas sensor based on Schottky barrier modulation as described in any one of claims 1-3 in NO2 detection.
Citation Information
Patent Citations
Two-dimensional thin-layer material gas sensor as well as preparation method and application thereof
CN114018988A
SnS-WSe2 contact construction method based on thermal evaporation and application
CN121240485A
Au-WS2-Au Van der Waals Schottky junction type photoelectric sensing unit, preparation and application
CN122269826A
